A conflituosidade no campo e as alternativas de acesso a justiça nos assentamentos de reforma agrária - Afonso, Adriano Henrique de Oliveira (2016)
This dissertation aims to analyze the conflictual in agrarian reform settlements on home territory and demonstrate the viability of alternative forms of access to justice , delimiting social and legal measures to this desideratum. In our country the agrarian reform is essentially an outstanding issue of final settlement, delayed for centuries, conducted in the last decades with more social approach, but still deficient in its implementation. Despite having your trigger the pressure of social movements, the national agrarian reform program is conducted by the Government, in a context essentially charged of tension and violence, in which the Brazilian government, based in the capitalist mold, aiming to serve the interests the established powers and the agrarian oligarchies is shown unable to respond to agrarian conflicts with a focus on social justice. In this sense, at first, we trace the history of the Brazilian agrarian training, legislative developments and situation in the current context. In sequence, will be analyzed the conflictual field and violence resulting therefrom, both real and symbolic and the inability of the criminal justice system and Brazilian prison responding to the occurrence of the offense on the field. Finally, it will be analyzed as has materialized the action - or inaction - of the public authorities in the field, to facilitate access to justice to the settlers peasants, analyzing the role of the main state institutions involved and the most effective alternatives to implement alternatives solutions to reduction of agrarian conflicts.